Control of Microgrid with Enhancement of Wind Power Evacuation. Issue 5 (October 2015) - Vanitha, V.; Varadharajan, Vivek; Viswanathan, Raghav; Harish, T.
Out of the available renewable energy sources in India, wind energy plays a dominant role accounting for nearly 68% of the total renewable power produced in the country. Out of which Tamil Nadu produces 7162 MW (38%) of the total capacity. A major problem faced by all wind farms in the state is that of evacuation of wind power due to limited power transmission capacity of existing transmission lines. Kudimangalam, one such wind farm in Coimbatore is taken up for study in this paper. By transforming this windfarm into a microgrid, wind power evacuation problems can be mitigated or minimized to a larger extent. The goal of this paper is to suggest the capacity of solar plant, gas power plant and battery storage to be used for the proposed microgrid. Energy Management Algorithm (EMA) is incorporated in MATLAB Simulink and is tested for different conditions. Finally implementation of EMA is done with the help of PIC microcontroller. From the study, it can be concluded that it is feasible to convert the considered wind farm into a microgrid with solar and gas power plants of appropriate capacity so that wind power is utilized to its maximum without power evacuation problems.